Does Inconsistent Social Support Matter? The Effects of Social Support on Work Absorption Through Relaxation at Work - Xu, Shan; Zhang, Youxin; Zhang, Bingran; Qing, Tao; Jin, Jiafei (Frontiers in Psychology, 2020)
Drawing upon conservation of resources theory and social exchange theory, we examined the effects of family-supportive supervisor behavior (FSSB) and family support (FS) on work absorption at the within- and between-person levels. A 10-day study of 91 workers using 710 observations was employed. At the within-person level, the results suggested that daily relaxation at work mediated the relationships between daily FS, daily shifts in FS, and daily work absorption. However, at the between-person level, the results revealed that chronic relaxation at work mediated the relation between the average level of FSSB/FS and chronic work absorption. We conclude that FSSB/FS plays a vital role in relaxation at work and work absorption at the within- and between-person levels.